Wczesna dramaturgia Jarosława Iwaszkiewicza na współczesnej scenie. „Kwidama” potyczki teatralne - Gracla, Jadwiga (Załącznik Kulturoznawczy, 2024)
The aim of this sketch is to show the stage potential of Iwaszkiewicz's text and to juxtapose it with the concept of Andrzej Dziuk, the creator of the stage realisation of the text. The play, entitled A Game for Everyone, was staged in 1984 at the Stary Theatre in Kraków. The performance utilised and creatively expanded elements characteristic of theatre: patterns, folk theatre characters, role-play awareness, text-performance. According to the author, Dziuk has aptly followed the tradition and tendency of the drama, and has used its theatrical potential. He has exposed the very aspects of theatricality, of play present in Iwaszkiewicz, taken from the theories of the author's contemporaries and using the experience of folk theatre, nativity plays and mysteries.